Facile synthesis of N-doped carbon layer encapsulated Fe2N as an efficient catalyst for oxygen reduction reaction. (February 2018) - Liu, Zaojin; Yu, Jing; Li, Xingyun; Zhang, Lixue; Luo, Dong; Liu, Xuehua; Liu, Xiaowei; Liu, Shuibo; Feng, Hongbin; Wu, Guanglei; Guo, Peizhi; Li, Hongliang; et al.
Abstract: Development of non-noble metal catalysts for oxygen reduction reaction (ORR) is of significant importance for the commercialization of fuel cells and metal-air batteries. Here we provide an efficient method to produce core-shell structured FeNC catalyst via a facile in-situ chelating strategy by introducing ammonia iron citrate during the polymerization process of dopamine. The influence of calcination temperature and atmosphere on the physicochemical property and the activity of the catalyst are systematically evaluated. By calcination at 800 °C with NH3 atmosphere, Fe2 N encapsulated with N doped carbon layers shows excellent activity with close onset and half wave potential (E1/2 ) while better methanol crossover resistance than the Pt/C catalyst. The high activity could be due to the synergistic effect of Fe2 N with the N-doped graphitic carbon layers and the mesoporous structure facilitating the mass transfer. Moreover, the simple synthesis process could provide a versatile routine to construct core-shell structured metal-NC composite for a wild catalytic application. Graphical abstract: Image 1